Manipulative Language and Power in Intimate Relationships: A Forensic Linguistic Analysis of Victim Testimony Narratives in ‘Luka dan Saksi’ (Chapter 21) of Broken Strings by Aurélie Moeremans - Niken Ardila Rehiraky (Austronesian: Journal of Language Science & Literature, 2026)
Research on intimate partner violence has shown that abuse is not only physical but also constructed through language; however, previous studies have largely focused on institutional discourse and have not systematically examined manipulative language in literary victim testimony. This study aims to analyze the linguistic strategies of manipulation and control in perpetrator discourse as reconstructed in the victim’s narrative in Chapter 21 (“Luka dan Saksi”) of Broken Strings (2023) by Aurélie Moeremans, and to examine how these strategies construct power asymmetry. This study adopts a qualitative approach integrating critical discourse analysis and forensic linguistics, focusing on micro linguistic features and macro social meanings. The data consist of 23 perpetrator utterances analyzed through a thematic and interpretive framework. The results reveal six recurrent patterns of manipulative strategies, namely threats and coercion, interrogative control, suicidal threats, gaslighting, victim blaming discourse, and emotional manipulation. These patterns demonstrate an observable escalation from implicit intimidation to more explicit forms of coercion. The findings show that linguistic features function to construct manipulation and sustain unequal power relations within intimate relationships. The study concludes that manipulative language operates as a form of discursive violence that reinforces coercive control. This research contributes to forensic linguistics by highlighting literary testimony as a valuable data source and by offering an integrative approach to analyzing manipulative discourse in non institutional contexts.